Wide band gap semiconductor nanowires, 2 : Heterostructures and optoelectronic devices - Consonni, Vincent; Feuillet, Guy (London, UK : ISTE, 2014)
This book, the second of two volumes, describes heterostructures and optoelectronic devices made from GaN and ZnO nanowires. Over the last decade, the number of publications on GaN and ZnO nanowires has grown exponentially, in particular for their potential optical applications in LEDs, lasers, UV detectors or solar cells. So far, such applications are still in their infancy, which we analyze as being mostly due to a lack of understanding and control of the growth of nanowires and related heterostructures. Furthermore, dealing with two different but related semiconductors such as ZnO and.
5.2. Top-down GaN-based axial nanowire LEDs5.2.1. Fabrication of top-down GaN-based axial nanowires; 5.2.2. Device fabrication of axial nanowire LEDs; 5.2.3. Performance characteristics of top-down axial nanowire LEDs; 5.3. Bottom-up GaN-based axial nanowire LEDs; 5.3.1. Growth techniques; 5.3.2. Doping, polarity and surface charge properties; 5.3.3. Design and typical performance of bottom-up axial nanowire LEDs; 5.3.3.1. Disk/well-in-a-wire LEDs; 5.3.3.2. Double heterostructure nanowire LEDs; 5.3.3.3. Dot-in-a-wire nanowire LEDs; 5.3.3.4. Polarization-induced p-n junction nanowire LEDs.
Includes bibliographical references.
Print version record.
Keywords: Optoelectronic devices; Nanowires; TECHNOLOGY & ENGINEERING -- Mechanical; Nanowires; Optoelectronic devices; Electronic books; Electronic books